PELATIHAN LARI SAMBUNG BACK TO BACK 20 METER ENAM REPETISI EMPAT SET DAN LARI SAMBUNG BACK TO BACK 30 METER EMPAT REPETISI EMPAT SET MENINGKATKAN KECEPATAN LARI 80 METER SISWA PUTRA SMP DHARMA PRAJA BADUNG - Gimbar Adiputra; alex pangkahila; I P G. Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
Type of 80 meters ran is one of the numbers on athletics competed in early age of child. In early age, the physical condition and mind can still be developed continuously and systematically. The exercise in early age should be an element of play and competition, thus this exercise is attempted to develop the speed by two types of exercise: back to back relay run of 20 meters six reps four sets and back to back relay run of 30 meters four reps four sets. The aim of research is to know the increasing of 80 meters speed of run. The exercise was conducted for six weeks with a frequency of three times a week with the aim to increasing the speed. The numbered of sample was 24 people selected randomly from junior high school students of Dharma Praja Badung that meets the requirements of inclusion and exclusion. The numbered of each group consists of twelve people. Each group was given a different treatment i.e. group I was treated by back to back relay run of 20 meters six reps and four sets and group II treated by back to back relay run of 30 meters four reps four sets. Data derived from the duration time of 80 meters ran before and after exercise, with t paired test to determine the difference average speed of duration time before and after exercise in each group. The t Unpaired test for the difference average of increased speed between two groups with significance limit of 0.05. The differences of speed in 80 meters ran after exercise in both groups showed significant differences, i.e. p = 0.000 (p